Factors associated with the risk of violence against older adult women: a cross-sectional study - Rute Costa Régis De Sousa; Gleicy Karine Nascimento De Araújo; Rafaella Queiroga Souto; Renata Clemente Dos Santos; Rafael Da Costa Santos; Luana Rodrigues de Almeida (Universidade de São Paulo, 2021)
Objective: to identify the factors associated with the risk of violence against older adult women. Method: this is a quantitative, analytical, and cross-sectional research conducted with 122 older adult females in the city of Recife, state of Pernambuco, Brazil. Data collection was carried out using validated instruments adapted to Brazil. The analysis was performed using descriptive statistics (absolute and relative frequency) and inferential statistics (Pearson's chi- square, Spearman's correlation test, and Multiple Logistic Regression). Results: there was prevalence of a risk of abuse against older adult women under 70 years of age, literate, without a stable relationship, living alone, without any work activity, and who had an income higher than the minimum wage. There is a significant association between the risk of violence among older women with a higher number of chronic health conditions (24; 77.4%), and who are less active in advanced activities (42; 70.0%). A reduction in quality of life and satisfaction with life, and the onset of depressive symptoms, increase the risk of violence. Conclusion: multimorbidity, low functional capacity, depressive symptoms, low quality of life and low satisfaction with life, a high number of chronic conditions, depressive symptoms, and functional dependence to perform daily activities can be conditioning factors for the emergence of abuse against older adults.